Effective Modulating Brassinosteroids Signal to Study Their Specific Regulation of Reproductive Development and Enhance Yield - Zu, Song-Hao; Jiang, Yu-Tong; Hu, Li-Qin; Zhang, Yan-Jie; Chang, Jin-Hui; Xue, Hong-Wei; Lin, Wen-Hui (Frontiers in Plant Science, 2019)
Brassinosteroid (BR) is a family of bioactive steroid hormones that plays vital roles in plant growth and development. The BR-mediated regulation of plant growth and architecture has been well studied. However, relatively few studies have investigated the BR-related regulation of reproductive development because of the difficulties in excluding non-specific regulation and secondary responses from severe vegetative phenotypes and poor nutritional status. Furthermore, differentially regulating the BR signal in vegetative and reproductive organs is problematic. Thus, establishing a method for modulating the BR signal only in reproductive organs or during reproductive developmental stages will be beneficial. Additionally, the utility of BR applications for crop production is limited because of deleterious side-effects, including the associated decrease in the planting density and lodging resistance. Moreover, enhancing the BR signal may lead to feedback inhibition. In this study, we developed a transformation system for modulating the BR signal differentially during reproductive and vegetative developmental stages. This system involves transformations with different combinations of a reproductive tissue-specific promoter, coding sequences that increase or decrease the BR signal, and various genotypic backgrounds with enhanced or decreased BR signals. The enhanced BR signal generated in transformants was targeted to reproductive organs without affecting vegetative organs. This system may be useful for studying the BR-specific regulation of plant reproductive development and shows promise for optimizing seed yield.